(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper deals with an environmental impact assessment of the Peruru Banda Hill comprising of granite, located at around 8 km west of Tiruchanur, Tirupati District, Andhra Pradesh, India before and after the construction of the Vakulamatha Temple by the Tirumala-Tirupati Devasthanams (TTD) in June 2022. Studies using multi-date Google Earth Pro (GEP) satellite images generated from the software available in the public domain revealed a remarkable improvement in the environmental condition of the temple portion of the Hill, while the remaining portion of the hill is either highly water-logged or marked with rugged hilly region at varying elevations owing to illegal mining by local artisans. This paper provides a methodology helpful to the TTD Engineering Department to transform the entire rocky and water-logged areas of the hill into a high-value prime land through appropriate mining of Peruru granite and conjunctive use of surface water and groundwater in the nearby Peruru Tank.